STX4 expression is associated with classification, clinical stage and lymphatic metastasis in ovarian cancer - Ye, Wenfeng; Zhu, Dawei; Xu, Bin; Xu, Ming; Liu, Yingting; Xie, Jun; Wang, Qi; Jiang, Jingting (Translational Cancer Research, 2019)
Background: Ovarian cancer (OC) is one of the most common malignant tumors in female reproductive system and 55–75% of the patients relapsed after surgery and standard postoperative chemotherapy and radiotherapy. The SNARE proteins, syntaxin4 (STX4) is localized in the plasma membrane to drive vesicle fusion which of integrin-containing vesicles with the plasma membrane is the final step of integrins delivery and play a role in the occurrence, development, invasion and metastasis of cancer cells. Methods: Immunohistochemistry analysis was used to investigate the correlation between STX4 expression and clinicopathological features of epithelial OC patients. Results: Our study demonstrated that STX4 was positively expressed in OC tissues and the expression of STX4 was positively correlated with the clinical stage of human OC classification and node metastasis, suggesting that STX4 was involved in the occurrence and development of OC. Conclusions: Our findings suggested that STX4-targeted treatment could be used as a potential therapeutic strategy for OC.